The crack kinking out of an interface - Veljković Jelena M. (Theoretical and Applied Mechanics, 2005)
Kinking of a plane strain crack out of an interface between the two dissimilar isotropic elastic materials is analyzed. Analysis is focused on the initiation of kinking and thus the segment of the crack leaving the interface is imagined to be short compared to the segment in the interface. The analysis provides the stress intensity factors and energy release rate of the kinked cracks in terms of the corresponding quantities for the interfacial crack. The energy release rate is enhanced if the crack heads into the more compliant material and is diminished if the crack kinks into the stiff material.